Efficacy of irrigation methods with varying levels of water in gerbera (Gerbera jamesonii L.) production (Journal of the Bangladesh Agricultural University, 2020)
Gerbera (Gerbera jamesonii L.) requires frequent fresh irrigation water in order to minimize water stress and accomplish maximum production and high quality flower. Salinity is the major constraint for gerbera cultivation in the southern part of Bangladesh. Rainwater preservation and its judicial use could have been an active area of research for gerbera cultivation in saline stressed areas. Drip system is a progressive method to irrigate larger area with minimum loss of water. Thus, an experiment was conducted following RCBD to investigate the efficacy of drip irrigation with stored rainwater and to optimize the water level for gerbera with 400, 500 and 600 ml water day-1 plant-1. Application of 500 ml water day-1 plant-1 by flood irrigation system was considered as control. The highest number of leaves plant-1 (56.20), leaf length (25.18 cm), leaf width (7.01 cm), number of flowers plant-1 (11.20) and flower diameter (5.25 cm) were recorded in plants irrigated by drip method with 500 ml water day-1 plant-1 but longest stalked flowers (23.58 cm) was produced by plants irrigated with same quantity of water (500 ml day-1) by conventional (flood) method. No significant differences between drip and flood method with equal quantity of water was observed for number of leaves plant-1, flower stalk length and flower diameter at 60 days after planting but significant variation was recorded for flowers plant-1. Drip irrigation method may be more suitable for irrigating gerbera field and application of 500 ml water day-1 plant-1 in drip method may be optimum for maximum flowering.J Bangladesh Agril Univ 18(1): 6–11, 2020https://doi.org/10.5455/JBAU.94715